(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
International Organisation for Standardisation (ISO) containers, designed to protect contents against extreme conditions, are often repurposed as temporary shelters during disasters, conflict, or urbanization. However, modifying these containers for housing greatly affects their structural integrity. Several studies have numerically and experimentally investigated the structural strength of container structures. However, there was limited information on the lateral stiffness of a residential ISO container subjected to lateral load. A piece of valuable information when the container is applied to a multi-story structure. This study proposed to conduct physical tests on two full-scaled residential ISO container structures to evaluate their lateral stiffness. Considering the actual condition of a residential container, both samples were fabricated with different sizes of openings. The finite element models of the samples were developed and analysed employing Abaqus for comparison with other studies and the experimental results. The application for lateral stiffness of ISO containers subjected to wind load was discussed based on the current design standard. The outcome of the study widened the scope of the structural behaviour of an ISO container towards the lateral stiffness of a residential container structure.